Eviscerations in a District Hospital in Ghana: A Five-Year Experience - Mathurin, Youfegan-Baanam; Prah, James Kojo; Akoto, Yaw Osei (International Journal of Health Sciences, 2022)
Purpose: Destructive eye surgeries have been described as necessary evils. Even though they are important and sometimes life-saving, their psychological impacts on the patients are many. This study sought to determine the prevalence and main indications of evisceration in Our Lady of Grace Hospital in the Asikuma-Odoben-Brakwa District of the Central Region of Ghana. Methodology: The mixed method study design was used. A five-year review of all cases of eviscerations from 2012-1016, was conducted. Also, in-depth interviews of 9 patients purposively selected, who had undergone eviscerations during the period under review were conducted. Data analysis was largely descriptive. Result: Out of a total of 2996 ocular surgeries conducted within the 5-year period, 101 were eviscerations. This gives a 5-year prevalence of 3.4 per 100 surgeries. Out of the 101 cases of eviscerations, 81 were included in the analysis due to the availability of complete data. The mean age of patients was 50 years (SD 1.53). The majority of patients who underwent eviscerations were 60 years and more. Right (51%) and left (49%) eyes were eviscerated in nearly equal proportion. The occupations of the majority of patients were farmers/fisherfolks (55.6%) and trading (19.8%). Most (76.5%) eviscerations were due to non-trauma-related causes mainly infections (55.6%). The trauma-related indications for evisceration (23.4%) were stick/vegetative materials, stone/particles, and assault. Unique Contribution to Theory, Policy and Practice: Eye infections and injuries which are largely preventable were the main causes of eviscerations in this study. Public education to encourage early reporting is needed. The aged should be discouraged from engaging in unprotected manual farm-related activities.